ANALISIS RENCANA KEBIJAKAN AKSI BERSIH SAMPAH KOTA PEKANBARU - M Fajar Anugerah; Mhd Rafi Yahya (LPPM Universitas Abdurrab, 2022)
The Pekanbaru City Government through the Environmental and Hygiene Service has prepared an Action Plan for the Pekanbaru City Waste Clean Area in 2017 which contains plans, strategies, policies, programs and activities to be carried out in waste management. The plan was made according to an evaluation study by looking at the current state of waste on the results of the development of Pekanbaru City. The purpose of this study is to describe the analysis of the Pekanbaru City waste clean action plan which is intended to formulate a concept of Pekanbaru City government policy on waste management. This study uses a qualitative method, this method is very suitable to be used in this study to analyze policy analysis in an effort to clean up waste in Pekanbaru City. The findings in this study are the first by way of the rationale for the need for an action plan for a clean waste area by making regional regulations that specifically regulate waste management in Pekanbaru. . Second, involvement in the clean-waste action plan policy by looking at how far the integration has been between the local cultural and social context, natural conditions, structures and institutions, available economic and technological conditions and skills.